Well-being of teachers depends on high job satisfaction - Lee, Cheng Ean Catherine *; Leow, Serena Wai Yee *; Leow, Kenneth (Star Media Group Berhad, 2023)
In the bustling landscape of education, one crucial aspect that is often overlooked is the well-being of teachers. The findings of a recent study showed that job satisfaction was a crucial factor in determining the overall well-being of high school teachers.